#Take idealized bodies out of the picture: A scoping review of social media content aiming to protect and promote positive body image. (September 2021) - Rodgers, Rachel F.; Paxton, Susan J.; Wertheim, Eleanor H.
Highlights: A scoping review identified 35 relevant studies including 24 specifically focused on social media. Images without individuals and those portraying diverse appearances are most helpful. Effects of text highlighting body acceptance or the unrealistic nature of social media are unclear. Findings are conflicting regarding the usefulness of social marketing strategies like hashtags. Abstract: Much evidence has highlighted detrimental effects of social media on body image, and attention has turned towards identifying content that could support and promote positive body image. This study aimed to conduct a scoping review of the emerging evidence focused on social media content that might support positive body image. A total of n = 35 studies (21 experimental) examining social media were identified along with n = 11 studies not specifically focusing on social media but with clear implications. Overall, findings suggest that images that do not portray individuals are most helpful for body image, as well as those portraying appearances diverging from appearance ideals. Our review also identifies types of social media content that have so far not been found to protect body image, and those not sufficiently evaluated. Regarding textual captions and comments, the most promising avenue involves highlighting the contrived and unrealistic nature of social media content. However, empirical data are limited and not robust. Body acceptance-related statements have so far not been found to be helpful for body image, and findings regarding the usefulness of using social marketing strategies (such as hashtags) to identify content that may be more realistic is nascent and conflicted.